The effectiveness of mindfulness based cognitive therapy on loneliness and rumination of veteran's spouses - A. Talebi; M. Zarnaghash (Afarand Scholarly Publishing Institute, 2020)
Aims: Veteranschr('39') families, especially their wives, are at high risk for mental and psychological injuries that should be noticed to them. The aim of present study was to investigate the effectiveness of mindfulness based cognitive therapy on loneliness and rumination of veterans' spouses. Materials & Methods: In this experimental study with pretest-posttest design with control group, 22 veterans' spouses of Shiraz city in 2018 were selected by purposive sampling method and randomly assigned into case and control groups (11 subjects in each group). Participants in both groups completed the DiTommaso's loneliness questionnaire and the Nolen-Hoeksema's rumination questionnaire. The case group was then subjected to mindfulness-based cognitive therapy intervention during 8 sessions of 120-150 minutes. After group therapy on the case group, the post-test was performed on both groups. Data were analyzed by SPSS 20 software, using dependent and independent t-tests. Findings: In case group, significant changes in the sense of loneliness and rumination scales were observed in the post-test compared to the pre-test (p=0.0001). However, no significant changes were observed in the control group. There was also a significant difference between the case group and the control group in the sense of loneliness (p=0.01) and rumination (p=0.001). Conclution: Mindfulness-based cognitive therapy is an effective strategy to reducing sense of loneliness, and rumination in veterans' spouses.